The Jurisprudence of Particularism National Identity Claims in Central Europe - Kovács, Kriszta (Bloomsbury Academic, 2023)
This open access book asks whether there is space for particularism in a constitutional democracy which would limit the implementation of EU law. National identity claims are a key factor in shaping our times and the ongoing evolution of the European Union. To assess their impact this collection focuses on the jurisprudence of Czechia, Hungary, Poland, and Slovakia, as they play an essential role in giving life to particularism. By taking particularism as the prism through which they explore the question, the contributors offer a new analytical scheme to evaluate the judicial invocation of identity. This requires an interdisciplinary approach: the study draws on comparative constitutional law, theory, comparative-empirical material and normative-philosophical perspectives. This is a fresh and thought-provoking new study on an increasingly important question in EU law. The ebook editions of this book are available under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.